EKSISTENSI PIDANA MINIMUM KHUSUS DALAM MENCEGAH DAN MEMBERANTAS TINDAK PIDANA KORUPSI DI INDONESIA - Abdul Bagas; Davit Rahmadan; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One of the most dangerous crimes in Indonesia is corruption, corruption isa white-collar crime and an extraordinary crime. The legal umbrella in dealingwith criminal acts of corruption in Indonesia to date is Law Number 20 of 2001concerning Amendments to Law Number 31 of 1999 concerning the Eradicationof Corruption Crimes, where the Law contains a special minimum sentence as areflection of the principle of legality, which contains elements of legalcertaintyand also as an effory to achieve more effective goals to prevent anderadicate corruption in Indonesia. However, when viewed from the number ofdecisions, this proves that the specific minimum sentence contained in the law hasnot been able to achieve its objective.This research is a normative research with a statute approach to determinelegal principles and norms which are criminal law policies in formulating specificminimum criminal concepts that are appropriate in preventing and eradicatingcriminal acts of corruption, using secondary data as data sources. Methods ofdata collection with a normative juridical approach in this study using libraryresearch techniques. The purpose of this study is to determine the existence of aspecial minimum sentence in preventing and eradicating corruption in Indonesiaand to find out the appropriate concept of a special minimum sentence inpreventing and eradicating corruption in Indonesia from a criminal perspective.From this research it can be concluded that the special minimum sentencecontained in the Law on the Eradication of Corruption Crimes in terms of itsimplementation is in accordance with laws and regulations, but in terms of theeffectiveness of the special minimum sentence it has not been implemented. able toreach his goal. namely the prevention and eradication of corruption. corruptionin Indonesia. Therefore, it is necessary to update the specific minimum crimescontained in the anti-corruption law, which are exacerbated by taking intoaccount the past or the crime itself and also paying attention to its future or goals.criminal punishment. Thus the special minimum sentence can reflect howdangerous the consequences or impacts of corruption are both for the state andfor all Indonesian people, and this can result in general prevention and specialprevention so that the special minimum punishment can achieve its own goals,namely preventing and eradicating corruption in Indonesia.Keywords : existence – Specific Minimum Punishment – Corruption